Neospora caninum infection and reproductive problems in dairy cows from Brazil: A case-control study - de Souza, Giovanna Gati [UNESP]; Amatti, Lidiana Zanetti; Garcia, Luana Venâncio; Costa, Letícia Ramos; Minutti, Ana Flávia; Martins, Thais Agostinho; Bogado, Alexey Leon Gomel; Ignácio, Fernanda Saules [UNESP]; de Almeida, Breno Fernando Martins; Garcia, João Luis; de Barros, Luiz Daniel [UNESP] (Elsevier, 2022)
Neosporosis, an infectious disease caused by the protozoan Neospora caninum, has been associated with economic losses in cattle rearing worldwide. However, previous studies have not presented any evidence regarding the association between serological status of neosporosis and alteration of the reproductive parameters. Thus, this study aimed to determine whether N. caninum is associated with reproductive disorders and to evaluate the possible risk factors of the infection. Blood samples from 202 dairy cows, 51 with a history of reproductive disorders (case group) and 151 without (control group), were collected from different farms in Brazil. Epidemiological questionnaires were conducted with all the farmers. Serum samples were subjected to an indirect fluorescent antibody test to detect antibodies against the parasite. In total, 28.22% (57/202) of the cows were seropositive: 47.06% (24/51) from the case group and 21.85% (33/151) from the control group. By logistic regression, cows aged ≥48 months and cows with history of abortion were 4.8 (95% confidence interval [CI] = 1.91–12.05; p = 0.001) and 2.3 (95% CI = 1.06–5.1; p = 0.034) times more likely to be seropositive, respectively. Furthermore, our results show an association between N. caninum seropositivity and abortion in dairy cows from Brazil with poor management conditions and N. caninum seropositivity risk factors for reproductive disorders.
Keywords: Abortion; Dairy science; Neosporosis; Reproductive disorders; Risk factors